2009
DOI: 10.1007/s11013-009-9161-3
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Processes and Perceived Helpfulness of Dang-Ki (Chinese Shamanism) from the Symbolic Healing Perspective

Abstract: This study focuses on the therapeutic process and perceived helpfulness of dang-ki, a form of Chinese shamanistic healing, in Singapore. It aims to understand the healing symbols employed in dang-ki, whether or not patients find them helpful and whether their perceived helpfulness can be explained by the symbolic healing model (Dow, Am Anthropol 88(1): 56-69, 1986; Levi-Strauss, Structural anthropology. Basic Books, New York, 1963). Although many researchers have applied this model to explain the efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…There are several theories of how ritual may bring about healing (Desjarlais, 1989;Dow, 1986;Frank & Frank, 1991;Kirmayer, 1993;Kleinman, 1980;Lee, Kirmayer, & Groleau, 2010;Le´vi-Strauss, 1963;Sax, Quack, & Reinhold, 2010). Most of these models emphasize what is common across diverse practices but the variety and specificity of healing practices has much to teach us.…”
mentioning
confidence: 99%
“…There are several theories of how ritual may bring about healing (Desjarlais, 1989;Dow, 1986;Frank & Frank, 1991;Kirmayer, 1993;Kleinman, 1980;Lee, Kirmayer, & Groleau, 2010;Le´vi-Strauss, 1963;Sax, Quack, & Reinhold, 2010). Most of these models emphasize what is common across diverse practices but the variety and specificity of healing practices has much to teach us.…”
mentioning
confidence: 99%
“…Subsequent studies have shown the emotional motivations of rituals such as praying, chanting, and using lucky charms in the face of acute failure or annihilation (Case et al, 2004 ; Burger and Lynn, 2005 ; Rudski and Edwards, 2007 ). Building on the insights of Levi-Strauss, medical sociologists and psychiatrists have argued that emotions evoked by rituals, within the multifaceted symbolism of myths, elicit a sense of meaningfulness for participants (Dow, 1986 ; Kirmayer, 2004 ; Lee, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, perceived helpfulness is likely to facilitate families' involvement, lead to more effective interventions, and improved outcome measures. Lee and colleagues (2010) reported that patients perceived the care and treatment to be helpful after experiencing improvements or changes in their physical (e.g., gastric relief, improved blood circulation, feeling more energetic), cognitive (e.g., reduction of anxiety, sense of calmness, security, self-awareness, hopefulness), or interpersonal (e.g., reduction of interpersonal conflicts) functioning (39). There are few studies exploring the factors influencing perceived helpfulness, but it appears that etiological information (attributed causes of mental health problems), past experiences, nature of treatments and expectations are important (4042).…”
Section: Introductionmentioning
confidence: 99%